Training offer selection and course timetabling for remedial education. (September 2017) - Ghiani, Gianpaolo; Manni, Emanuele; Romano, Alessandro
Highlights: Training offer selection and timetabling for remedial courses. A mathematical model and a heuristic are proposed. For large-sized instances the heuristic outperforms the exact approach. Abstract: Remedial education aims to assist students that need to achieve particular competencies in several skills at different levels. In this article, we model and solve the problem of selecting the training offer and the related timetabling for high-school remedial courses subject to a number of common budget and operational constraints. We propose an Integer Programming formulation as well as a heuristic to quickly find feasible solutions of good quality for large scale instances. Our algorithms are then tested on randomly-generated instances resembling real-world situations. Computational results show that the exact approach becomes not viable as the size of the instances grows, while the heuristic achieves a good trade-off between solution quality and running time.